CONSTRUCTIONS OF NON-CATEGORICAL STATEMENTS IN ENGLISH AND RUSSIAN (COMPARATIVE ANALYSIS) - Mukhamedova Nigora (Bright Mind Publishing, 2025)
This article presents a comparative analysis of non-categorical statement constructions in English and Russian. Non-categorical statements—those expressing uncertainty, probability, or subjectivity—play a vital role in nuanced communication and reflect the speaker’s attitude toward the information conveyed. The study explores structural, lexical, and grammatical means used to construct such statements in both languages, with particular attention to modal verbs, particles, introductory phrases, and syntactic patterns. By examining parallel examples, the analysis identifies both convergences and divergences in how English and Russian express non-categorical meanings. Findings suggest that while both languages employ similar communicative strategies, they differ in the frequency and stylistic preference for certain constructions, often reflecting broader typological distinctions and cultural attitudes toward epistemic modality.
Keywords: Non-categoric statements, Modality, English-Russian comparison, Epistemic expressions, Modal verbs, Subjectivity in language, Comparative linguistics, Syntax and modality, Cross-linguistic analysis, Uncertainty in communication.